Assessment of powder mixed EDM: A review - Nanimina, A.M. (EDP Sciences, 2014)
This project research undertakes the assessment of powder added electrical discharge machining (PMDM) with focus on effect of additive powders and circulation systems. In PMEDM process, powder can be mixed with dielectric fluid either in the main EDM tank or in a separate tank in order to improve EDM machining performance. Different designs of powder mixed EDM circulating systems such as closed and opened systems with different sizes of tank are described in literature. Various devices such as stirrer, circulating pump etc. are placed in the tank in order to ensure the uniformity of powder mixed dielectric. Each design has its advantages and disadvantages and it might affect the EDM output results. Therefore, there is a need to review the PMEDM with respect to additive powders and circulation systems in order to identify the gap and propose an alternative for improving process. Â© 2014 Owned by the authors, published by EDP Sciences.